Does the ultraviolet radiation affect the germination of Fagopyrum esculentum Moench seeds? - Stefanello, Raquel; Bevilaqua, Daiane Balconi; Garcia, Wagner Jesus da Silva (Disciplinarum Scientia | Naturais e Tecnológicas, 2023)
Light is essential to growth and development throughout the life cycle of plants. Plants modify their morphological traits in response to a varying intensity and quality of light signals. Observations regarding the parameters that impact seed germination are critical for understanding the germination process. Thus, this research analyzed the effect of ultraviolet radiation (UV-B and UV-C) on buckwheat seed germination. Initially, the seeds were exposed to UV radiation for various amounts of time (doses) (0, 1h, 2h, 4h, and 8h). They were sown on germitest paper and stored in a Biochemical Oxygen Demand chamber set at 20 °C and a 12-hour photoperiod. Tests were conducted for germination, first count, length, and dry mass of seedlings. The exposure of buckwheat seeds to UV-B and UV-C radiation did not significantly affect germination and seedling root length. However, a decrease in shoot length was observed with higher doses of UV radiation. These findings suggest that buckwheat seeds exhibit relative tolerance to UV-C radiation, while showing some sensitivity to UV-B radiation.